The Effectiveness of Advanced Platelet-Rich Fibrin in comparison with Leukocyte-Platelet-Rich Fibrin on Outcome after Dentoalveolar Surgery - Alaa Z. Makki; Anoud M. Alsulami; Arwa S. Almatrafi; Moroj Z. Sindi; Shahinaz N. Sembawa (International Journal of Dentistry)
Background and Purpose. Some physiological changes may occur following tooth extraction, and symptoms during the postextraction period may affect the patient’s quality of life. Many techniques have been developed to improve postextraction pain and soft tissue healing. Accordingly, this study will compare the postextraction pain and early soft tissue healing characteristics of extraction sites treated with leukocyte-platelet-rich fibrin (L-PRF) and advanced platelet-rich fibrin (A-PRF). The aim is to evaluate the effect of advanced PRF in comparison with L-PRF on soft tissue healing and pain after teeth extraction and to advice dental practitioner to use the advanced PRF in clinic to enhance soft tissue healing and decrease pain. Methods. The study included 60 patients according to sample size calculation, recruited from patients seeking tooth extraction at oral and maxillofacial surgery clinic at Umm Al-Qura University, Faculty of Dentistry. Patients were divided into three groups. Group Ӏ included 20 patients managed by advanced platelet-rich fibrin after extraction. Group ӀӀ included 20 patients managed by leukocyte-platelet-rich fibrin after tooth extraction. Group ӀII included 20 patients left without any addition. Each group was further subdivided into surgical and nonsurgical extraction. Afterwards, patients in each group were assessed for postextraction pain by VAS, number of analgesics, and early soft tissue healing by LWHI. Results. The study outcomes demonstrate that the use of A-PRF significantly reduces postoperative pain in the 1st and 2nd day. VAS pain scores on the first day were significantly higher in the control surgical extraction group and L-PRF nonsurgical extraction group. In early soft tissue healing. The Landry Wound Healing Index (LWHI) was used after 1 and 2 weeks of extraction to evaluate the extraction site. In first week, the A-PRF group and L-PRF group (nonsurgical extraction) had a better healing index when compared to control group, and A-PRF group (surgical extraction) had a best healing index when compared to L-PRF and control groups. In the second week, individuals in the A-PRF group (surgical and nonsurgical extraction) had a better healing index when compared to L-PRF and control groups.